Synaptonemal complex analysis of Nellore and Gyr breeds of Bos taurus indicus - Da Paixão Scavone, Márcia Denise [UNESP]; Oliveira, Claudio [UNESP]; Trinca, Luzia Aparecida [UNESP]; Foresti, Fausto [UNESP] (Firenze University Press, 2000)
A synaptonemal complex (SC) study of specimens of Nellore and Gyr breeds of Bos taurus indicus was performed with the main objective to identify and determinate the frequency of abnormalities of SC and the frequency of cells with abnormalities. All animals analyzed had 29 autosomal bivalents and one sexual bivalent. The Nellore breed had 30.00% of cells with SC abnormalities while the Gyr breed had only 11.11%. Statistical analyses showed that there were not significant differences for the number of cells with abnormalities among the breeds studied. The subspecies Bos taurus indicus had 16.92% of cells showing abnormalities, being 62.82% of these abnormalities in zygotene and 37.18% in pachytene. Some aspects regarding the frequency of cells with abnormalities and the fertility of Nellore and Gyr breeds are discussed.
Keywords: Bos taurus indicus; Cattle; Meiosis; Synaptonemal complex; Synaptonemal complex failure